Pater est quem nuptiae demonstrant in Switzerland: comparative perspective - Wudarski, Arkadiusz (Journal of the Belarusian State University. Law, 2022)
The statutory presumption of paternity of the mother’s husband causes many problems and – contrary to common belief – does not always protect the child’s best interest. The paper examines the impact of this legal principle on family life and considers its viability in today’s society. The research focuses on Swiss law but also makes references to German and Polish regulations. In a broader sense, the analysis is made from the perspective of the biological father, who is not the legal father. Based on a critical analysis, the new approaches of intentional parenthood, multiple parents and consensual change of paternity are discussed. Concluding that the mother’s marital status cannot determine the child’s affliation, the author recommends a more ﬂexible solution.